Organocatalytic Enantioselective Functionalization of Unactivated Indole C(sp3)−H Bonds - Ma, Dengke; Zhang, Zhihan; Chen, Min; Lin, Zhenyang; Sun, Jianwei (Angewandte Chemie International Edition, 2019)
Described here is a direct catalytic asymmetric functionalization of unactivated alkyl indoles using organocatalysis. In the presence of an effective chiral urea catalyst and a phosphoric acid additive, the intermolecular C−C bond formation between alkyl indoles and trifluoropyruvates proceeded with high efficiency and enantiocontrol. Unlike previous asymmetric C(sp3−H) functionalizations of α‐azaarenes, this process does not require the use of either a strong base or an electron‐deficient substrate. The excellent enantiocontrol is particularly noteworthy in view of the severe background reaction as well as the complete inability of other types of catalysts evaluated. Control experiments, kinetic studies, and DFT calculations provided important insights into the mechanism. Not just one, but two: An organocatalytic asymmetric functionalization of unactivated benzylic C(sp3)−H bonds of alkyl indoles with trifluoropyruvates was developed with high enantioselectivity. Mechanistic studies and DFT calculations show an unusual mechanism, including the first installation of a trifluoropyruvate electrophile at C3 of indoles, towards the formation of the key enamine nucleophile, followed by the addition of the second trifluoropyruvate.